Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti dengan Model Problem Bases Learning (PBL) Melalui Media Power Point pada Materi Gereja Sebagai Umat Allah dan Persekutuan Yang Terbuka Kelas XI SMA Negeri 1 Silimakuta - Hermal Fererius Lingga (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research is a collaborative class action research (PTKK) carried out in class XI 6 SMA Negeri 1 Silimakuta with a total of 33 students consisting of 12 male students and 21 female students. This study aims to see whether the problem base learning model with powerpoint media can improve student learning outcomes in reviewing church material as God's people and open fellowship. This research is divided into two cycles, each of which consists of identifying problems, planning, implementing actions, observing and collecting data, analyzing data, and reflecting and improving. Data collection was carried out using tests. The results of the study showed that there was an increase in students' learning ability with powerpoint media on the material to increase students' ability in the Church's material for the environment, as evidenced by the average value of student learning outcomes at the end of the first cycle of 65.75 or 27% and at the end of the second cycle was 73.39 or 69.69%. From the results of the study, it can be concluded that learning using the problem base learning model with powerpoint media can improve students' abilities in the material of the Church as the People of God and Open Communion.in grades XI-6 SMA N 1 Silimakuta.